Urgensi Pendidikan Pancasila dalam Membentuk Karakter Generasi Bangsa - Juwono, Hendro; Syahid, Mar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2024)
Indonesia as part of a pluralistic country consists of people with different cultural, ethnic, religious, or linguistic backgrounds. On the one hand, these differences are a Grace from Allah SWT that needs to be cared for and maintained. On the other hand, diversity has the potential to cause conflicts between ethnicities, groups, and beliefs. So far, the Ministry of Religious Affairs has promoted Religious Moderation as a pioneer in moderating the understanding and attitudes of extremes that occur. This article discusses the role of Pancasila Education in shaping the nation's character with a descriptive qualitative research method. The type of research is Pustaka. The results of the study concluded that character education cultivation can be done in three ways, first through inclusion in the Educational Curriculum. Pancasila values must be introduced to students in schools, so it is necessary to include Pancasila values in the curriculum that is enforced. Second, strengthen Pancasila-based character education. Acquaint children with nationalist characters, such as mutual cooperation, visiting sick friends, collaborating in completing projects with friends, and helping each other in succeeding activities outside the home. And third, to ensure a healthy environment for the nation's generation. An environment that instills Pancasila values, serves children from less positive backgrounds.